Bibliometric Analysis of Social Entrepreneurship in Education: Mapping of Keywords, Research Topics and Geographical Distribution of Global Research (2019-2024) - Arhas, Sitti Hardiyanti; Wahira, Wahira (Program Pascasarjana Universitas Negeri Makassar, 2024)
This study aims to analyze the current trends in social entrepreneurship, especially in social entrepreneurship education, using a bibliometric approach. This study is relevant considering the importance of social entrepreneurship in creating social change and supporting sustainable development goals. The main objectives of this study are to identify keywords that frequently appear in related literature, map relevant topics, and explore the geographical distribution of research worldwide in the 2019-2024 time frame. The method used involves collecting data through the Publish or Perish application from two major databases, namely Scopus and Google Scholar, then analyzing it using Mendeley to identify author keywords. Further bibliometric analysis was carried out using VOSviewer to map the relationships between keywords and distribute the research geographically. The results show that keywords such as